COMPARISON OF LIMB LENGTH DISCREPANCY IN CHILDREN WITH FEMUR SHAFT FRACTURE TREATED WITH PRIMARY HIP SPICA VERSUS SECONDARY HIP SPICA. - Farhad Alam; Zain Ur Rehman; Muhammad Kaleem Shaukat (Journal of University Medical & Dental College, 2019)
INTRODUCTION: Shaft of femur fractures are frequently occurring fractures of lower extremities requiring hospital admission especially in children. Most of them have been treated by closed methods. Good blood supply of femur shaft allows rapid healing with favorable outcomes after non- operative treatment generally. OBJECTIVE: To compare primary hip spica cast and secondary hip spica cast in treatment of fractured femur shaft in children less than 6 years age in terms of frequency of discrepancy in limb length. STUDY DESIGN: Randomized control trial. SETTINGS: Orthopedic department of Allied and DHQ hospital FSD and Madina teaching hospital Faisalabad. DURATION OF STUDY: 18-05-2016 to 18-05-2017 SUBJECTS & METHODS: All children with age group 6 months to 6 years were admitted and randomly divided into two. (Group A included those treated with primary hip spica cast and Group B included those treated with secondary hip spica cast.) After six weeks of follow-up limb length discrepancy was assessed. RESULTS: A total 310 cases as per inclusion/exclusion criteria were enrolled. Mean and standard deviation for age was calculated as 36.43+16.117 months. Gender distribution showed that 81.6%( n=253) were male and 18.4 %( n=57) were females. Frequency of shortening of length was recorded in 9 %(n=28) patients that included 5.2%(n=8) from the primary hip spica group and 12.9%(n=20) from the secondary hip spica group. CONCLUSION: We concluded that primary hip spica casting is an eﬀective and reliable method for treating femoral shaft fractures in children age 5 month to 6 years with union rate of 100%. It is safe, eﬀective and low cast with low frequency of limb length discrepancy as compared to secondary hip spica cast. We therefore recommend it as a ﬁrst line of treatment for closed simple transverse and short oblique diaphyseal femoral fracture in children age 5 months to 6 years.